CT-Scan Based Evaluation of Dorsal-to-Ventral Ratios of Paraspinal Musculature in Chondrodystrophic and Non-chondrodystrophic Dogs - Hartmann, Katinka; Düver, Pia; Kaiser, Stephan; Fischer, Carolin; Forterre, Franck (Frontiers in Veterinary Science, 2020)
Objective: To assess and objectively quantify, with CT-scan exams, differences in cervical paraspinal musculature and intervertebral-disk conformation that might influence the different predispositions for anatomical localizations of intervertebral-disk disease observed in chondrodystrophic and non-chondrodystrophic breeds. Sample: Retrospective evaluation and analysis of cervical spine CT-scans performed on 30 dogs presented for clinical reasons unrelated to a cervical disk problem. 15 chondrodystrophic (Dachshunds) and 15 non-chondrodystrophic dogs (Labrador Retrievers) were included. Procedures: Height measurements of dorsal and ventral paraspinal musculature were performed on sagittal CT-scan reconstructions to generate dorsal-to-ventral height ratios. Additionally, disk angulation to the floor of the vertebral canal was determined for each cervical disk. On transverse plane images the areas of the dorsal and the ventral paraspinal musculature were measured and ratios calculated. Furthermore, estimations of moments exerted on the disk were evaluated through calculation of a dorsal-to-ventral ratio of moments applied at the level of each disk. Results: Dachshunds showed a relatively more prominent dorsal paraspinal musculature than Labrador Retrievers with statistically significant higher dorsal-to-ventral height ratios at C3/C4 (p = 0.034), C4/C5 (p = 0,004) and at C7/T1 (p = 0.004) and dorsal-to-ventral area ratio at C3/C4 (p < 0.001). Regarding the disk angle to the spinal canal floor along the cervical spine, Labrador Retrievers had a less steep conformation compared to Dachshunds with a significant difference at C2/C3 (p < 0.001). Relation of moments calculation revealed statistically significant differences at C2/C3 (p = 0.021). Conclusion and Clinical Relevance: In the cervical spine, height and area ratios along with ratio of moments showed significant differences affecting anatomical and biomechanical dorsal-to-ventral paraspinal muscle relationship as well as disk angulation between chondrodystrophic and non-chondrodystrophic dogs, especially in the upper cervical spine. These differences may play a role in the development of intervertebral disk disease, nevertheless further studies are needed to fully explain the real pathophysiological value of the present findings.